Basalt Fiber Composite Material-Modified Heavy-Duty Asphalt Mixture, Its Preparation Method and Application

By loading UiO-67-NH2 onto basalt fibers and modifying basalt fiber composites with amino-modified chitin whiskers, the problem of weak interfacial bonding strength between basalt fibers and asphalt was solved, the overall performance of asphalt mixtures was improved, and the pavement requirements under heavy traffic conditions were met.

CN120271274BActive Publication Date: 2025-10-28HENAN JIAO YUAN ENG TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510448225.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-10
Publication Date
2025-10-28
Estimated Expiration
2045-04-10

AI Technical Summary

Technical Problem

Traditional asphalt materials are difficult to meet the road surface requirements under heavy traffic conditions. The interfacial bond strength between basalt fiber and asphalt is weak, making it difficult to fully utilize its excellent mechanical properties.

Method used

Modified basalt fiber composite material was used to prepare heavy-duty asphalt mixture by loading MOF material UiO-67-NH2 onto basalt fibers to enhance their adsorption and bonding force with asphalt, and by using amino-modified chitosan whiskers to improve the affinity and bonding strength of the composite material.

Benefits of technology

It improves the low-temperature crack resistance, high-temperature rutting resistance, water stability and fatigue resistance of asphalt mixtures, and enhances the load-bearing capacity and crack resistance of asphalt pavements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005353230770000081
    Figure BDA0005353230770000081
  • Figure BDA0005353230770000091
    Figure BDA0005353230770000091
Patent Text Reader

Abstract

This invention relates to asphalt mixtures, and more particularly to heavy-duty asphalt mixtures modified with basalt fiber composite materials, their preparation methods, and applications. The heavy-duty asphalt mixture modified with basalt fiber composite materials comprises, by weight, the following raw materials: 10-15 parts asphalt, 1-3 parts modified basalt fiber, 1-3 parts amino-modified chitosan whiskers, 85-90 parts mineral aggregate, 5-8 parts hollow glass microspheres, 3-6 parts compatibilizer, and 1-3 parts stabilizer. The modified basalt fiber improves the asphalt mixture's low-temperature crack resistance, high-temperature rutting resistance, and water stability, while the amino-modified chitosan whiskers improve the asphalt mixture's fatigue resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to asphalt mixtures, and more particularly to heavy-duty asphalt mixtures modified with basalt fiber composites, their preparation methods, and applications. Background Technology

[0002] With the rapid development of my country's economy, highway traffic conditions are characterized by heavy loads, high traffic volumes, and significant channelization. These traffic conditions place increasingly higher demands on the quality of asphalt pavements, and traditional asphalt materials are insufficient to meet the pavement requirements under heavy traffic conditions. Therefore, modifying asphalt to improve its high and low temperature performance and road performance has become an urgent research task in the building materials field.

[0003] Basalt fiber is a novel high-performance inorganic fiber that has emerged in recent years, possessing excellent properties such as high strength, high modulus, high temperature resistance, and corrosion resistance. Compared with other fibers, basalt fiber exhibits significant advantages in asphalt pavement applications, such as superior mechanical properties, acid and alkali resistance, aging resistance, and good water stability. These characteristics make basalt fiber an ideal material for improving road performance (such as fatigue resistance, water damage resistance, and crack resistance). However, due to its low surface energy, weak asphalt adsorption capacity, and lack of strong interfacial bonding strength, basalt fiber's excellent mechanical properties in asphalt mixtures are difficult to fully realize. Therefore, it is necessary to modify basalt fiber to address the engineering problems caused by its weak asphalt adsorption capacity and interfacial bonding ability. Summary of the Invention

[0004] In order to overcome the shortcomings of the prior art, one of the objectives of this invention is to provide a heavy-duty asphalt mixture modified based on basalt fiber composite material, which has excellent properties.

[0005] The second objective of this invention is to provide a simple method for preparing heavy-duty asphalt mixtures modified with basalt fiber composite materials.

[0006] The third objective of this invention is to provide applications for heavy-duty asphalt mixtures modified with basalt fiber composite materials, which has broad application prospects.

[0007] One of the purposes of the present invention is achieved by the following technical solution:

[0008] The modified heavy-duty asphalt mixture based on basalt fiber composite material includes the following raw materials by weight: 10-15 parts asphalt, 1-3 parts modified basalt fiber, 1-3 parts amino-modified chitin whiskers, 85-90 parts mineral aggregate, 5-8 parts hollow glass microspheres, 3-6 parts compatibilizer, and 1-3 parts stabilizer.

[0009] Furthermore, the hollow glass microspheres have a particle size of 0.1-0.5 μm.

[0010] Furthermore, the preparation method of the modified basalt fiber is as follows:

[0011] 2-Amino-4,4'-biphenyldicarboxylic acid and zirconium tetrachloride were added to a mixed solution of glacial acetic acid and DMF, and then pretreated basalt fibers were added to react. After purification, modified basalt fibers were obtained.

[0012] Furthermore, the ratio of 2-amino-4,4'-biphenyl dicarboxylic acid, zirconium tetrachloride, and pretreated basalt fiber in the mixed solution is 4g:(5-6)g:4g:(300-400)mL; the volume ratio of glacial acetic acid and DMF in the mixed solution is 1:(4-6).

[0013] Furthermore, the reaction temperature is 115-130℃, and the reaction time is 20-24h.

[0014] Furthermore, the preparation method of the pretreated basalt fiber is as follows: wash the basalt fiber with acetone solution, dry it, soak it in NaOH solution, and then purify it.

[0015] Furthermore, the basalt fibers have a diameter of 10-15 μm and a length of 3-8 mm.

[0016] Further, the volume concentration of the acetone solution is 20-30%; the concentration of the NaOH solution is 2-4 mol / L; the soaking temperature is 50-60℃, and the soaking time is 0.5-1.5 h.

[0017] Further, the preparation method of the amino-modified chitin whiskers is as follows: chitin is dispersed in a 5-6 mol / L hydrochloric acid solution and reacted at 90-100℃ for 4-6 h, and chitin whiskers are obtained after purification; chitin whiskers are dispersed in deionized water at a mass ratio of γ-aminopropyltriethoxysilane to chitin whiskers of 1:(5-8), γ-aminopropyltriethoxysilane is added, and the mixture is reacted at 55-65℃ for 3-6 h, and then purified.

[0018] Furthermore, the compatibilizer is tall oil, the stabilizer is sulfur, and the mineral aggregate is composed of basalt aggregate and limestone mineral powder; the mass ratio of the basalt aggregate to the limestone mineral powder is 9:1.

[0019] Furthermore, the basalt aggregate is composed of basalt aggregates with particle sizes of 10-30mm, 5-10mm, and 0-3mm, with a mass ratio of 1.5:1.5:1.

[0020] The second objective of this invention is achieved by the following technical solution:

[0021] The above-mentioned method for preparing heavy-duty asphalt mixture modified with basalt fiber composite material includes the following steps:

[0022] Weigh the raw materials according to the stated weight proportions, heat the asphalt to a molten state, and then add modified basalt fiber, amino-modified chitin whiskers, mineral materials, hollow glass microspheres, compatibilizer and stabilizer. Shear and stir at 175-180℃ for 1-2 hours to obtain the final product.

[0023] The third objective of this invention is achieved by the following technical solution:

[0024] The above-mentioned application of heavy-duty asphalt mixture modified with basalt fiber composite material in road surface paving.

[0025] Furthermore, when using the modified heavy-duty asphalt mixture based on basalt fiber composite material for road surface paving, the modified basalt fibers are also woven into a grid and laid between the pavement layers. This technical solution can significantly improve the load-bearing capacity, rutting resistance, fatigue resistance, crack resistance, and water damage resistance of heavy-duty asphalt pavements.

[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0027] This invention provides a modified heavy-duty asphalt mixture based on basalt fiber composite material, wherein the modified basalt fiber is obtained by loading basalt fiber onto MOF material UiO-67-NH2. UiO-67-NH2 has a large pore size, pore volume, and specific surface area, and its surface contains negatively charged adsorption centers, enabling it to strongly adsorb asphalt and increase the adsorption bonding force with asphalt. Furthermore, UiO-67-NH2 contains amino groups, which can form hydrogen bonds and van der Waals forces with asphalt, thereby improving the adhesion between the two. After modification with UiO-67-NH2, the compatibility and wettability between basalt fiber and asphalt are improved, the bond strength between basalt fiber and asphalt is increased, and the asphalt and composite fiber material form a homogeneous and stable mixture, effectively improving the stability of the asphalt mixture, including low-temperature crack resistance, high-temperature rutting resistance, and water stability. The aminated chitin whiskers of the present invention are chitin whiskers treated with γ-aminopropyltriethoxysilane. The above modification can not only reduce the hygroscopicity of chitin whiskers, but also enhance the affinity of chitin whiskers with various raw materials. Appropriate addition can increase the viscosity and toughness of asphalt mortar, thereby effectively improving the fatigue resistance of asphalt mixture. Detailed Implementation

[0028] The present invention will be further described below with reference to specific embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments. Specific conditions not specified in the embodiments shall be performed according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, all reagents or instruments used are conventional products obtained through commercial channels.

[0029] The mineral aggregate involved in this invention is composed of basalt aggregate and limestone powder in a mass ratio of 9:1; the basalt aggregate is composed of basalt aggregate with particle sizes of 10-30mm, 5-10mm, and 0-3mm, with a mass ratio of 1.5:1.5:1; the basalt fiber has a diameter of 10-15μm and a length of 3-8mm; the hollow glass microspheres have a particle size of 0.1-0.5μm; and the asphalt is No. 70 Grade A asphalt.

[0030] Example

[0031] Example 1

[0032] Example 1 provides a modified heavy-duty asphalt mixture based on basalt fiber composite material. The mixture is composed of the following raw materials by weight: 12 parts of No. 70 Grade A asphalt, 2 parts of modified basalt fiber, 2 parts of amino-modified chitin whiskers, 87 parts of mineral aggregate, 6 parts of hollow glass microspheres, 5 parts of tall oil, and 2 parts of sulfur.

[0033] The preparation method of the above-mentioned modified basalt fiber is as follows:

[0034] Basalt fibers were washed with a 25% (v / v) acetone solution to remove surface impurities, dried, and then soaked in a 3 mol / L NaOH solution at 55°C for 1 hour. They were then washed successively with ethanol and deionized water, and dried to obtain pretreated basalt fibers. Following a ratio of 4 g:5.5 g:4 g:350 mL for 2-amino-4,4'-biphenyl dicarboxylic acid, zirconium tetrachloride, pretreated basalt fibers, and a mixed solution, 2-amino-4,4'-biphenyl dicarboxylic acid and zirconium tetrachloride were added to a mixed solution of glacial acetic acid and DMF (v / v = 1:5), followed by the addition of the pretreated basalt fibers. The mixture was reacted at 120°C for 2 hours, filtered to obtain a solid product, washed with deionized water, and dried in a vacuum oven at 80°C for 24 hours to obtain modified basalt fibers.

[0035] The specific preparation method of the above-mentioned amino-modified chitin whiskers is as follows:

[0036] Chitin was dispersed in a 5 mol / L hydrochloric acid solution and reacted at 95 °C for 5 h. The solid product was obtained by centrifugation, dialyzed, and lyophilized to obtain chitin whiskers. Chitin whiskers were dispersed in deionized water at a mass ratio of γ-aminopropyltriethoxysilane to chitin whiskers of 1:7. γ-aminopropyltriethoxysilane was added and reacted at 60 °C for 5 h. After filtration, washing with deionized water, and drying in a vacuum oven at 50 °C for 24 h, amino-modified chitin whiskers were obtained.

[0037] Example 1 also provides a method for preparing the above-mentioned heavy-duty asphalt mixture modified based on basalt fiber composite material, as follows:

[0038] Weigh the raw materials according to the stated weight proportions, add No. 70 Grade A asphalt to a mixing shear mill and heat to a molten state, then add modified basalt fiber, amino-modified chitin whiskers, mineral aggregate, hollow glass microspheres, tall oil and sulfur, and shear and stir at 175℃ for 2 hours to obtain the final product.

[0039] Example 2

[0040] Example 2 provides a modified heavy-duty asphalt mixture based on basalt fiber composite material. The mixture is composed of the following raw materials by weight: 10 parts of No. 70 Grade A asphalt, 1 part of modified basalt fiber, 1 part of amino-modified chitin whiskers, 85 parts of mineral aggregate, 5 parts of hollow glass microspheres, 3 parts of tall oil, and 1 part of sulfur.

[0041] The preparation method of the above-mentioned modified basalt fiber is as follows:

[0042] Basalt fibers were washed with a 20% (v / v) acetone solution to remove surface impurities, dried, and then soaked in a 2 mol / L NaOH solution at 50°C for 1.5 h. They were then washed successively with ethanol and deionized water, and dried to obtain pretreated basalt fibers. Following a ratio of 4 g:5 g:4 g:300 mL for 2-amino-4,4'-biphenyl dicarboxylic acid, zirconium tetrachloride, pretreated basalt fibers, and a mixed solution, 2-amino-4,4'-biphenyl dicarboxylic acid and zirconium tetrachloride were added to a mixed solution of glacial acetic acid and DMF (v / v = 1:4), followed by the addition of the pretreated basalt fibers. The mixture was reacted at 115°C for 24 h, filtered to obtain a solid product, washed with deionized water, and dried in a vacuum oven at 80°C for 24 h to obtain modified basalt fibers.

[0043] The specific preparation method of the above-mentioned amino-modified chitin whiskers is as follows:

[0044] Chitin was dispersed in a 6 mol / L hydrochloric acid solution and reacted at 90 °C for 6 h. The solid product was obtained by centrifugation, dialyzed, and lyophilized to obtain chitin whiskers. Chitin whiskers were dispersed in deionized water at a mass ratio of 1:5 of γ-aminopropyltriethoxysilane and chitin whiskers. γ-aminopropyltriethoxysilane was added and reacted at 55 °C for 6 h. After filtration, washing with deionized water, and drying in a vacuum oven at 50 °C for 24 h, amino-modified chitin whiskers were obtained.

[0045] Example 2 also provides a method for preparing the above-mentioned heavy-duty asphalt mixture modified based on basalt fiber composite material, as follows:

[0046] Weigh the raw materials according to the specified weight proportions, add No. 70 Grade A asphalt to a mixing shear mill and heat it to a molten state, then add modified basalt fiber, amino-modified chitin whiskers, minerals, hollow glass microspheres, tall oil and sulfur, and shear and stir at 185℃ for 1 hour to obtain the final product.

[0047] Example 3

[0048] Example 3 provides a modified heavy-duty asphalt mixture based on basalt fiber composite material. The mixture is composed of the following raw materials by weight: 15 parts of No. 70 Grade A asphalt, 4 parts of modified basalt fiber, 2 parts of amino-modified chitin whiskers, 90 parts of mineral aggregate, 8 parts of hollow glass microspheres, 6 parts of tall oil, and 3 parts of sulfur.

[0049] The preparation method of the above-mentioned modified basalt fiber is as follows:

[0050] Basalt fibers were washed with a 30% (v / v) acetone solution to remove surface impurities, dried, and then immersed in a 4 mol / L NaOH solution at 60°C for 0.5 h. They were then washed sequentially with ethanol and deionized water, and dried to obtain pretreated basalt fibers. Following a ratio of 4 g:6 g:4 g:400 mL for 2-amino-4,4'-biphenyl dicarboxylic acid, zirconium tetrachloride, pretreated basalt fibers, and a mixed solution, 2-amino-4,4'-biphenyl dicarboxylic acid and zirconium tetrachloride were added to a mixed solution of glacial acetic acid and DMF (v / v = 1:6), followed by the addition of the pretreated basalt fibers. The mixture was reacted at 130°C for 24 h, filtered to obtain a solid product, washed with deionized water, and dried in a vacuum oven at 80°C for 24 h to obtain modified basalt fibers.

[0051] The specific preparation method of the above-mentioned amino-modified chitin whiskers is as follows:

[0052] Chitin was dispersed in a 6 mol / L hydrochloric acid solution and reacted at 100 °C for 4 h. The solid product was obtained by centrifugation, dialyzed, and lyophilized to obtain chitin whiskers. Chitin whiskers were dispersed in deionized water at a mass ratio of γ-aminopropyltriethoxysilane to chitin whiskers of 1:8. γ-aminopropyltriethoxysilane was added and reacted at 65 °C for 3 h. After filtration, washing with deionized water, and drying in a vacuum oven at 50 °C for 24 h, amino-modified chitin whiskers were obtained.

[0053] Example 3 also provides a method for preparing the above-mentioned heavy-duty asphalt mixture modified based on basalt fiber composite material, as follows:

[0054] Weigh the raw materials according to the stated weight proportions, add No. 70 Grade A asphalt to a mixing shear mill and heat to a molten state, then add modified basalt fiber, amino-modified chitin whiskers, mineral aggregate, hollow glass microspheres, tall oil and sulfur, and shear and stir at 175℃ for 1.5 hours to obtain the final product.

[0055] Comparative Example

[0056] Comparative Example 1

[0057] Comparative Example 1 provides an asphalt mixture, which is composed of the following raw materials by weight: 12 parts of No. 70 Grade A asphalt, 2 parts of basalt fiber, 2 parts of amino-modified chitin whiskers, 87 parts of mineral aggregate, 6 parts of hollow glass microspheres, 5 parts of tall oil, and 2 parts of sulfur. The preparation method of amino-modified chitin whiskers is the same as that in Example 1.

[0058] Comparative Example 1 also provides a method for preparing the above-mentioned asphalt mixture, which is consistent with that of Example 1.

[0059] Comparative Example 2

[0060] Comparative Example 2 provides an asphalt mixture composed of the following raw materials by weight: 12 parts of No. 70 Grade A asphalt, 2 parts of modified basalt fiber, 2 parts of chitin whiskers, 87 parts of mineral aggregate, 6 parts of hollow glass microspheres, 5 parts of tall oil, and 2 parts of sulfur. The preparation method of the modified basalt fiber is consistent with that of Example 1.

[0061] Comparative Example 2 also provides a method for preparing the above-mentioned asphalt mixture, which is consistent with that of Example 1.

[0062] The application effects of the mixture obtained by the present invention will be described below.

[0063] According to JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", the low-temperature crack resistance, freeze-thaw splitting strength ratio, water immersion residual stability, Marshall stability, and rutting dynamic stability of the mixtures in Examples 1-3 and Comparative Examples 1-2 were tested. The fatigue resistance of each mixture was tested according to NF P 98-261-1. The test results are shown in Table 1.

[0064] Table 1

[0065]

[0066]

[0067] The performance test results above show that: (1) the maximum bending strain data indicates that the low-temperature crack resistance of the mixtures obtained in Examples 1-3 of this invention is effectively improved; (2) the freeze-thaw splitting strength ratio and water immersion residual stability data indicate that the water stability of the mixtures obtained in Examples 1-3 of this invention is effectively improved; (3) the Marshall stability and dynamic stability data indicate that the high-temperature rutting resistance of the mixtures obtained in Examples 1-3 of this invention is effectively improved; and (4) the four-point bending fatigue life data indicate that the fatigue resistance of the mixtures obtained in Examples 1-3 of this invention is effectively improved. In summary, the mixtures obtained in Examples 1-3 of this invention have excellent comprehensive performance.

[0068] Compared to Examples 1-3, the properties of the mixtures in Comparative Examples 1-2 were reduced. Analysis revealed that Comparative Example 1 used basalt fiber instead of modified basalt fiber, and Comparative Example 2 used chitosan whiskers instead of aminated chitosan whiskers. Further analysis showed that UiO-67-NH2 has a large pore size, pore volume, and specific surface area, and its surface contains negatively charged adsorption centers, which can strongly adsorb asphalt, increasing the adsorption and bonding force with asphalt. Furthermore, UiO-67-NH2 contains amino groups, which can form hydrogen bonds and van der Waals forces with asphalt, thereby improving the adhesion between the two. After being modified with UiO-67-NH2, the compatibility and wettability between basalt fiber and asphalt were improved, the bond strength between basalt fiber and asphalt was increased, and the asphalt and composite fiber material formed a uniform and stable mixture, effectively improving the low-temperature crack resistance, high-temperature rutting resistance, and water stability of the asphalt mixture.

[0069] Chitosan whiskers treated with γ-aminopropyltriethoxysilane not only reduce the hygroscopicity of chitosan whiskers, but also enhance the affinity between chitosan whiskers and various raw materials. Appropriate addition can increase the viscosity and toughness of asphalt mortar, thereby effectively improving the fatigue resistance of asphalt mixtures.

[0070] The above embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and replacements made by technicians in this field on the basis of the present invention fall within the scope of protection required by the present invention.

Claims

1. A heavy-duty asphalt mixture modified with basalt fiber composite material, characterized in that, The raw materials include the following by weight: 10-15 parts asphalt, 1-3 parts modified basalt fiber, 1-3 parts amino-modified chitin whiskers, 85-90 parts minerals, 5-8 parts hollow glass microspheres, 3-6 parts compatibilizer, and 1-3 parts stabilizer. The modified basalt fiber is prepared as follows: 2-Amino-4,4'-biphenyl dicarboxylic acid and zirconium tetrachloride were added to a mixed solution of glacial acetic acid and N,N-dimethylformamide, and then pretreated basalt fibers were added to react. After purification, modified basalt fibers were obtained. The method for preparing the pretreated basalt fiber is as follows: wash the basalt fiber with acetone solution, dry it, soak it in NaOH solution, and then purify it.

2. The heavy-duty asphalt mixture modified with basalt fiber composite material according to claim 1, characterized in that, The volume ratio of 2-amino-4,4'-biphenyl dicarboxylic acid, zirconium tetrachloride, and pretreated basalt fiber in the mixed solution is 4 g: (5-6) g: 4 g: (300-400) mL; the volume ratio of glacial acetic acid and N,N-dimethylformamide in the mixed solution is 1: (4-6).

3. The heavy-duty asphalt mixture modified with basalt fiber composite material according to claim 1, characterized in that, The reaction temperature is 115-130℃, and the reaction time is 20-24h.

4. The heavy-duty asphalt mixture modified with basalt fiber composite material according to claim 1, characterized in that, The volume concentration of the acetone solution is 20-30%; the concentration of the NaOH solution is 2-4 mol / L; the soaking temperature is 50-60℃, and the soaking time is 0.5-1.5 h.

5. The heavy-duty asphalt mixture modified with basalt fiber composite material according to claim 1, characterized in that, The preparation method of the amino-modified chitin whiskers is as follows: chitin is dispersed in a 5-6 mol / L hydrochloric acid solution and reacted at 90-100℃ for 4-6 h. After purification, chitin whiskers are obtained. Chitin whiskers are dispersed in deionized water at a mass ratio of γ-aminopropyltriethoxysilane to chitin whiskers of 1:(5-8). γ-aminopropyltriethoxysilane is added and reacted at 55-65℃ for 3-6 h. After purification, the chitin whiskers are obtained.

6. The heavy-duty asphalt mixture modified with basalt fiber composite material according to claim 1, characterized in that, The compatibilizer is tall oil, the stabilizer is sulfur, and the mineral aggregate is composed of basalt aggregate and limestone mineral powder; the mass ratio of the basalt aggregate to the limestone mineral powder is 9:

1.

7. The method for preparing heavy-duty asphalt mixture modified based on basalt fiber composite material according to any one of claims 1-6, characterized in that, Includes the following steps: Weigh the raw materials according to the stated weight proportions, heat the asphalt to a molten state, and then add modified basalt fiber, amino-modified chitin whiskers, mineral materials, hollow glass microspheres, compatibilizer and stabilizer. Shear and stir at 175-180℃ for 1-2 hours to obtain the final product.

8. The application of basalt fiber composite modified heavy-duty asphalt mixture according to any one of claims 1-6 in road surface paving.

Citation Information

Patent Citations

  • Aminated micro-nano chitin-based acrylic resin and preparation method thereof

    CN114805634A

  • Modified cement stabilized macadam and preparation method thereof

    CN117534415A